Παράγοντες που σχετίζονται με τη μη αναφορά φαρμακευτικών λαθών από νοσηλευτές - Μιχαήλ, Σώτια (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2011)
Background: The problem of medication administration errors (MAE) is real and increasingly getting larger negatively affecting the quality of health services and undermining the credibility of nursing science. Aim: This paper aims of this critical literature review was to investigate the factors associated with non-reporting MAE among nurses. Sample and method: Α critical review of applied research literature. The material was found by searching the databases EMBASE, MEDLINE, SCOPUS, CINAHL and PUBMED. As key words used: medication administration errors, error reporting, nurses, factors. They found 26 articles related to this, but wake option used only 7. Results: The main factor was associated with non-reporting MAE among nurses is fear. Other factors were the uncertainty of nurses, the rank, the workload, the management system, reactions of their colleagues, but not to lose the trust of patients. Conclusion: Prevention is key MAE, the same record the MAE as to make prevention MAE should be recognized first and then grow and develop ways to prevent these causative factors. The MAE is not mentioned all, so much of the MAE after not listed, then either treated. It is therefore necessary to clarify the reasons for not reporting the MAE so that the recognition of these becomes possible to address them.
Keywords: Medication Errors--prevention & control; Risk Management --organization & administration